Insight into the Reaction Mechanism of (La0.58Sr0.40)(Co0.20Fe0.80)O3-δ Cathode with Volatile Chromium Species at High Current Density in a Solid Oxide Fuel Cell Stack. Issue 10 (13th June 2017) - Beez, Alexander; Yin, Xiaoyan; Menzler, Norbert H.; Spatschek, Robert; Bram, Martin
Abstract : Anode-supported solid oxide fuel cells with different Cr protection layers on the metallic interconnect were operated in a short stack at 700°C for 1240 h. The current density was raised sequentially from 0.5 A cm −2 during the first 240 h of operation to 0.75 A cm −2 for a further 1000 h. After operation, the (La, Sr)(Co, Fe)O3-δ (LSCF) cathode layers were analyzed with respect to Cr interaction by both wet chemical and microstructural methods. For cells equipped with interconnects coated with a dense APS protection layer, the amount of Cr on the cathode was in the range of a few μg. For cells with a porous WPS coating on the interconnect, the amount of Cr was in the range of 110–160 μg cm −2 and Cr-containing phases were detected by SEM analysis both on top of the cathode layer and also at the LSCF/GDC interface, which has rarely been observed before. In addition, a deterioration of the cathode microstructure near the LSCF/GDC interface was observed. With respect to the high current density during operation, a theory was developed which explains both the Cr deposition at the LSCF/GDC interface and also the deterioration of the cathode.